Ochrona zabytków w miejscowym planie zagospodarowania przestrzennego - Jaworska, Malwina (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The objective of this work is to present the subject of historic preservation in local zoning plans, including mainly the presentation of its essence in the light of the requirements of historic and cultural preservation and modern culture property preservation. It also seemed to be justifiable to relate to the topic of the planning authority of local governments, and the requirements of respecting the rules and procedures of preparing and enacting the local zoning acts. The choice of this topic created a necessity to present the role of a provincial voivodal historic preservation offices, who is equipped with tools to influence the essential nature of zoning plans. In order to achieve the above stated objectives, it was necessary to conduct an analysis of the historic preservation and protection law and the zoning law, as well as to refer to decisions of the administrative court.
Keywords: ochrona zabytków; miejscowy plan zagospodarowania przestrzennego